The Psychological Motivations of Nazism and Its Effect on the Superego According to Judith Kestenberg - Fátima Caropreso (Critical Hermeneutics)
Judith Kestenberg conducted extensive research into child victims of Nazi persecution. She sought not only to understand the psychological effects of the traumatic experiences and persecution experienced by those children but also to understand the psychological processes behind Nazi ideology and behavior. The objective of this article is to present some of her hypotheses about how Nazi ideology acted on both  the victims’  and the Germans’ superegos, as well as to address her conception of the psychological motivations for Nazism. The author claims that Nazism managed to invade the superegos of both Germans and some of the victims, which meant that, in the case of the latter, the persecution continued, even after the end of the Nazi regime. She also states that the children of Nazis were also victims of this regime, whose ultimate motivation would be the Germans’ impulse to kill their own children.